2008
DOI: 10.1371/journal.pone.0002396
|View full text |Cite
|
Sign up to set email alerts
|

Non-Syndromic Tooth Agenesis in Two Chinese Families Associated with Novel Missense Mutations in the TNF Domain of EDA (Ectodysplasin A)

Abstract: Here we report two unrelated Chinese families with congenital missing teeth inherited in an X-linked manner. We mapped the affected locus to chromosome Xp11-Xq21 in one family. In the defined region, both families were found to have novel missense mutations in the ectodysplasin-A (EDA) gene. The mutation of c.947A>G caused the D316G substitution of the EDA protein. The mutation of c.1013C>T found in the other family resulted in the Thr to Met mutation at position 338 of EDA. The EDA gene has been reported resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 28 publications
4
26
1
Order By: Relevance
“…Recently, there have been several reports of mutations in the EDA-A1 gene leading to an isolated form of X-linked recessive hypodontia (XLRH) [7,10,11,12]. This observation was somewhat surprising, since perturbation of the EDA-A1 pathway is also implicated in the development of hair and sweat glands.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there have been several reports of mutations in the EDA-A1 gene leading to an isolated form of X-linked recessive hypodontia (XLRH) [7,10,11,12]. This observation was somewhat surprising, since perturbation of the EDA-A1 pathway is also implicated in the development of hair and sweat glands.…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, a Chinese study reported p.Asp316Gly mutation in EDA protein to be associated with non-syndromic congenital tooth agenesis affecting every tooth type. All affected members show differential expression [93]. Mutations detected so far in EDA and related genes are summed up in Tables 4-6.…”
Section: Eda1 Genementioning
confidence: 99%
“…The mutation is located in the TNFL domain of the EDA protein. Several mutations in the TNFL domain have previously been reported (8,9,22). Schneider et al (9) showed that all missense mutations in the TNFL domain resulted in abolished or impaired binding of EDA to its receptors.…”
Section: Mutationsmentioning
confidence: 99%
“…Affected males showed most or all of the typical phenotypes of XLHED. However, only a few studies have reported the relationship between nucleotide substitution and protein structure (8,21,22).In this study, we analyzed the ED1 gene in two unrelated Japanese patients with XLHED, and we identified two novel Abbreviations: DHPLC, denaturing high-performance liquid chromatography; EDA, ectodysplasin-A; HED, hypohidrotic ectodermal dysplasia; TNFL, tumor necrosis factor ligand; XLHED, X-linked HED 0031-3998/09/6504-0453 PEDIATRIC RESEARCH …”
mentioning
confidence: 99%
See 1 more Smart Citation